Determination of Chemical, Nutritional and Fermentation Properties of Citrus Pulp Silages - Selma Büyükkılıç Beyzi; İsmail Ülger; Mahmut Kaliber; Yusuf Konca (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to investigate the possibilities of making silage from fruit juice industry waste.For this purpose, orange, lemon and tangerine pulp silage quality have been determined by comparing silage with maize and beet pulp silage.Treatment groups; 1) orange, 2) tangerine, 3) lemon, 4) maize and 5) sugar beet pulp. The silages were evaluated after 2 months from ensiling in the following areas: subjective evaluation, pH, dry matter, organic matter, crude protein, acid detergent fiber, neutral detergent fiber, ether extract and energy values (metabolizable energy) and net energy for lactation were calculated. As a result, it was determined that fruit juice industry residues were lower in terms of dry matter, but they contained higher energy due to their high organic matter content, digestibility and low cellulose content. In addition, it was determined that citrus pulp was evaluated as silage without any contribution.